Cytotoxic, anti-HIV–1 and anti-inflammatory activities of lanostanes from fruits of Garcinia speciosa - Pailee P. (2017)
© 2017 Phytochemical Society of Europe Bioassays-guided isolation of the hexanes and ethyl acetate extracts of the fruits of Garcinia speciosa led to the isolation of three new lanostane triterpenes 1–3 together with three related known derivatives 4–6. The new structures elucidated on the basis of spectroscopic and X-ray diffraction techniques were identified to be methyl (22E,24E)-9α-hydroxy-3-oxolanosta-22,24-dien-26-oate (1), (22E,24E)-9α,11β-dihydroxy-3-oxolanosta-22,24-dien-26-oic acid (2), and (24E)-23-acetoxy-3-oxolanosta-9,24-dien-26-oic acid (3), namely garciosaterpenes D, E and F, respectively. All compounds were evaluated for their cytotoxic and anti-inflammatory activities along with anti-HIV–1 activity. Most of the compounds were found inactive in the cytotoxic assay except for compound 6 which exhibited selective cytotoxicity against a KB cell line. All compounds showed significant inhibitory activities against HIV–1 reverse transcriptase (RT) assay and in the syncytium inhibition assay. Compounds 1, 5 and 6 displayed promising inhibitory activity in anti-inflammatory process.